QTc interval, cardiovascular events and mortality in patients with atrial fibrillation. (1st February 2018) - Reusser, Andreas; Blum, Steffen; Aeschbacher, Stefanie; Eggimann, Lucien; Ammann, Peter; Erne, Paul; Moschovitis, Giorgio; Di Valentino, Marcello; Shah, Dipen; Schläpfer, Jürg; Manser, Samuel; Reichlin, Tobias; et al.
Abstract: Background: A longer QTc interval has been associated with more adverse cardiovascular events and death in the general population. Little evidence is available on these relationships among patients with atrial fibrillation (AF). Methods: We performed a prospective observational multicenter cohort study of 1413 patients with AF. A resting 12‑lead electrocardiogram (ECG) was performed at baseline. QT interval was corrected for heart rate using the Bazett formula (QTc). Endpoints for this study included hospitalizations for congestive heart failure (CHF), a combination of cardiovascular death, myocardial infarction, stroke, systemic arterial embolism (MACE) and all-cause mortality. Results: Mean age of our population was 68 ± 12 years and 420 (30%) participants were female. Median QTc was 432 ms (interquartile range 409; 457). The mean follow-up time was 3.6 ± 1.5 years. After multivariable adjustment, there was a linear increase in risk with increasing QTc interval for incident CHF (hazard ratio (HR) per 1-SD increase in QTc 1.3 [95% CI 1.1; 1.6], p  = 0.008), MACE (HR 1.2 [1.0; 1.4], p  = 0.02) and all-cause mortality (HR 1.3 [1.0; 1.6], p  = 0.002). Results were consistent whether or not patients were in sinus rhythm on the baseline ECG (HR for CHF 1.7 versus 1.3, p interaction 0.08; HR for MACE 1.3 versus 1.2, p interaction 0.9; HR for all-cause mortality 1.4 versus 1.4, p interaction 0.9). Conclusions: In this large well-characterized cohort of AF patients, QTc interval was independently associated with adverse outcomes. These results were independent of the rhythm on the baseline ECG. Highlights: There is a significant association of QTc interval with various outcome events. The results are independent of rhythm and QRS duration. QT interval and corrected QT interval are highly predictive of future events in patients with atrial fibrillation.